2017
DOI: 10.1128/aem.00326-17
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Binding Studies of Bacillus thuringiensis Cry1Ac, Cry1F, Cry1C, and Cry2A Proteins in the Soybean Pests Anticarsia gemmatalis and Chrysodeixis (Pseudoplusia) includens

Abstract: Anticarsia gemmatalis (velvetbean caterpillar) and Chrysodeixis includens (soybean looper, formerly named Pseudoplusia includens) are two important defoliating insects of soybeans. Both lepidopteran pests are controlled mainly with synthetic insecticides. Alternative control strategies, such as biopesticides based on the Bacillus thuringiensis (Bt) toxins or transgenic plants expressing Bt toxins, can be used and are increasingly being adopted. Studies on the insect susceptibilities and modes of action of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 54 publications
2
22
1
1
Order By: Relevance
“…The effects of several Cry toxins have been previously demonstrated in larvae of A. gemmatalis (Bel et al, ; Mushtaq et al, , ; Fiuza et al, ). The mode of action and toxicity of some different Cry toxins were recently described by Mushtaq et al () and indicated that the domain III of Cry1Ac, which has a lectin fold, is not important for toxicity.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The effects of several Cry toxins have been previously demonstrated in larvae of A. gemmatalis (Bel et al, ; Mushtaq et al, , ; Fiuza et al, ). The mode of action and toxicity of some different Cry toxins were recently described by Mushtaq et al () and indicated that the domain III of Cry1Ac, which has a lectin fold, is not important for toxicity.…”
Section: Resultsmentioning
confidence: 90%
“…It is known that the binding of Cry toxin to target proteins results in the formation of pores in the cell membrane leading to cell death and tissue degradation (Gomez et al, ; de Maagd, Bravo, & Crickmore, ). In Brazil, transgenic soybean expressing Cry1Ac (one type of Bt toxin) has been commercialized since 2013 (Bel, Sheets, Tan, Narvac, & Escriche, ). The effect of Cry toxins against A. gemmatalis has been previously described, but its receptor still remains unidentified (Fiuza, Knaak, Fernando, Antônio, & Henriques, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of Cry2Ac7 domain III determined that out of the N506, Q509, and Y513 amino acid residues in Cry1Ac involved in binding to GalNAc [ 14 ], only Q509 is conserved. Consequently, we designed a toxin hybrid (H1.2Ac) combining domains I and II from Cry1Ac as the most active Bt toxin against A. gemmatalis and C. includens , and domain III from Cry2Ac7 as a novel toxin with toxicity against both species but predicted not to share binding sites with Cry1Ac [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that H1.2Ac and Cry1Ac are equally active against A. gemmatalis larvae supports the finding that interactions with the binding sites recognized by domain III of Cry1Ac may not be relevant to toxicity against A. gemmatalis . Dependence on domain III for recognition of this second population of Cry1Ac binding sites in A. gemmatalis BBMV would also help explain why GalNAc significantly inhibited Cry1Ac binding to BBMV from C. includens, while the effect was more modest on Cry1Ac binding to A. gemmatalis BBMV [ 18 ]. Interestingly, previous reports suggest the existence of two populations of Cry1Ac binding sites in C. includens , but not in A. gemmatalis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%